Using Paper as Reinforcement in Silty Sand - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications Inc, 2012)
Reinforced soil has been among the most effective soil modification materials. Its use has been expanded rapidly into civil engineering, geotechnical engineering and pavement engineering. Reinforcing subgarde in pavement systems has always been an issue. This study focuses on effect of paper inclusion on the modulus of elasticity of subgrade material. Paper was used for this investigation. Paper contents and aspect ratio have been changed during these tests. The paper percentage varied from 0 % (for unreinforced samples) to 20%. Silty sand was used as sub grade material. Unconfined compression tests were carried out to investigate behaviour of the composite under different condition. The paper reinforcment length and paper reinforcment content found to play important rule on the modulus of elasticity of paper reinforced samples. Furthermore it was observed that ductility of sample increased by paper inclusion.